Incidence of Jaundice in Preterm and Full Term Infants Admitted to Al-Zahraa learning hospital at An-Najaf Province - Ahmed Hassan Kudhair (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: One of the most predominant medical issues is the yellow coloration of the skin and scleraand it called Jaundice. It is occurred mostly in infants and could be either to a normal progress of gettingworse in to an irreversible brain damage. It could affect infants before 24 hour after birth and it consideredas pathological or after one day and now it regarded as physiological.Methods: One hundred and fifty child had been chosen in a prospective study that had been conducted inAl-Zhraa hospital at An-Najaf province. Those children were either a preterm or full term neonates and theirages were 0-14 days after admission to neonatal care unite or pediatric a ward in the hospital. The study wasstarted from the1st of October 2018 till Jane 30th 2019.The results showed the most of patient suffer from jaundice were those delivered at premature and those howtake breast feeding but not bottle feeding. Twenty eight percent of them were suffered from hemolysis dueto ABO-incompatibility, sepsis, preterm-maturity and Rh-incompatibilityConclusion: Jaundiceis a serious medical symptoms than should be controlled before induce uncontrolledcomplication that could be ends with permanent disability or even death